1999
DOI: 10.1074/jbc.274.30.21362
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical and Functional Characterization of Full-length, Recombinant Human Tissue Inhibitor of Metalloproteinases-2 (TIMP-2) Produced in Escherichia coli

Abstract: Matrix metalloproteinases (MMPs) function in the remodeling of the extracellular matrix that is integral for many normal and pathological processes. The tissue inhibitor of metalloproteinases family, including tissue inhibitor of metalloproteinases-2 (TIMP-2), regulates the activity of these multifunctional metalloproteinases. TIMP family members are proteinase inhibitors that contain six conserved disulfide bonds, one involving an amino-terminal cysteine residue that is critical for MMP inhibitor activity. TI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
106
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(125 citation statements)
references
References 28 publications
12
106
0
2
Order By: Relevance
“…ALA + TIMP-2 is a TIMP-2 mutant containing an additional amino terminal alanine, which renders it unable to inhibit MMPs (Wingfield et al 1999). As such, while ALA + TIMP-2 cannot inhibit MMPs directly, or activate proMMPs, it is still capable of binding to cell surface receptors, such as α3β1 integrin, and inducing integrin signaling (Seo et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…ALA + TIMP-2 is a TIMP-2 mutant containing an additional amino terminal alanine, which renders it unable to inhibit MMPs (Wingfield et al 1999). As such, while ALA + TIMP-2 cannot inhibit MMPs directly, or activate proMMPs, it is still capable of binding to cell surface receptors, such as α3β1 integrin, and inducing integrin signaling (Seo et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…As TIMP-2 signaling requires its selective interaction with integrin a3b1 (Seo et al, 2003;Oh et al, 2004;Perez-Martinez and Jaworski, 2005), we sought to determine the effects of TIMP-2 on the phosphorylation status of FAK and Src. Human microvascular endothelial cells (hMVECs) were treated with 100 nM recombinant human TIMP-2 (Wingfield et al, 1999) and cell lysates analysed by immunoblotting using phosphospecific antibodies. It was found that TIMP-2 increases the phosphorylation levels of FAK at both Tyr-397, the autophosphorylation site, and Tyr-925, known as a docking site for the adaptor Grb2 (Parsons, 2003) (Figure 1a).…”
mentioning
confidence: 99%
“…For example, TIMP-1 stimulates the proliferation of erythroid precursors (Gasson et al, 1985), and both TIMP-1 and TIMP-2 can positively influence the proliferation of numerous cell types (Hayakawa et al 1992(Hayakawa et al , 1994Wingfield et al, 1999). Additionally, TIMP-2 inhibits in vitro proliferation of human microvascular endothelial cells stimulated with bFGF (Murphy et al, 1993), and TIMP-3 promotes apoptosis (Ahonen et al, 1998;Baker et al, 1998), possibly through stabilization of TNF alpha receptors (Smith et al, 1997).…”
mentioning
confidence: 99%